Cyclophosphamide loaded thermo-responsive hydrogel system synergize with a hydrogel cancer vaccine to amplify cancer immunotherapy in a prime-boost manner - Fan Yang; Kun Shi; Ying Hao; Yanpeng Jia; Qingya Liu; Yu Chen; Meng Pan; Liping Yuan; Yongyang Yu; Zhiyong Qian (Bioactive Materials, 2021)
Although neoantigen-based cancer vaccines show great potential in cancer immunotherapy due to their ability to induce effective and long-lasting anti-tumor immunity, their development is hindered by the limitations of neoantigens identification, low immunogenicity, and weak immune response. Cyclophosphamide (CTX) not only directly kills tumors but also causes immunogenic cell death, providing a promising source of antigens for cancer vaccines. Herein, a combined immunotherapy strategy based on temperature-sensitive PLEL hydrogel is designed. First, CTX-loaded hydrogel is injected intratumorally into CT26 bearing mice to prime anti-tumor immunity, and then 3 days later, PLEL hydrogels loaded with CpG and tumor lysates are subcutaneously injected into both groins to further promote anti-tumor immune responses. The results confirm that this combined strategy reduces the toxicity of CTX, and produces the cytotoxic T lymphocyte response to effectively inhibit tumor growth, prolong survival, and significantly improve the tumor cure rate. Moreover, a long-lasting immune memory response is observed in the mice. About 90% of the cured mice survive for at least 60 days after being re-inoculated with tumors, and the distant tumor growth is also well inhibited. Hence, this PLEL-based combination therapy may provide a promising reference for the clinical promotion of chemotherapy combined with cancer vaccines.